2022
DOI: 10.3389/fbuil.2022.966281
|View full text |Cite
|
Sign up to set email alerts
|

An overview on seismic analysis of masonry building aggregates

Abstract: Conservation of historical centres is a pressing need for Mediterranean countries, that are characterized by masonry aggregates representing the most typical construction type within cities. Masonry clustered buildings were usually designed without seismic design criteria. Moreover, the current seismic standard codes do not foresee a clear calculation method to predict their non-linear behaviour. For this reason, in this paper, a wide overview on the seismic response of masonry aggregates has been done conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Previous seismic events and research into these events have shown the importance of the position in the block [40,[46][47][48][49][50] and the pounding effects [38,51] between adjacent buildings on the seismic vulnerability. The seismic performance of masonry building aggregates is often affected by the presence of fragile and deformable floor membranes, along with asymmetrical geometries.…”
Section: Urban Positionmentioning
confidence: 99%
“…Previous seismic events and research into these events have shown the importance of the position in the block [40,[46][47][48][49][50] and the pounding effects [38,51] between adjacent buildings on the seismic vulnerability. The seismic performance of masonry building aggregates is often affected by the presence of fragile and deformable floor membranes, along with asymmetrical geometries.…”
Section: Urban Positionmentioning
confidence: 99%
“…In many European countries, historic urban areas are generally characterized by unreinforced masonry (URM) buildings commonly clustered in aggregated configurations [1][2][3][4][5]. These buildings, due to their construction and evolution history, were not built in a unique phase but they were gradually 'assembled' over time through a process of merging, expanding, and modifying the original structures.…”
Section: Introductionmentioning
confidence: 99%
“…Macro-modelling has typically been the preferred approach for modelling complex historical masonry buildings (e.g. churches, towers, fortresses) [11,[14][15][16] or complex structural systems such as building aggregates [17][18][19] because it represents a good compromise between results' reliability and computational effort, especially when the buildings to be analysed are considerably large. Indeed, the computational effort of FE macro-model analyses is considerably lower than comparable analyses conducted using detailed and simplified FE micromodelling [20,21].…”
Section: Introductionmentioning
confidence: 99%